The Influence of Debt to Equity Ratio (DER), Return on Assets (ROA) and Company Size on Profit Growth - Dwi Joko Siswanto; Faschruella Maudhiky; Ickhsanto Wahyudi; Tantri Yanuar Rahmat Syah (Journal of Social Science, 2022)
This research was conducted to analyze the effect of Debt to Equity Ratio (DER), Return on Assets (ROA) and Firm Size on Profit Growth in Transportation Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) 2016-2019 either partially or simultaneously. The sampling method is purposive sampling. The number of samples used in this study were 9 transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) with a total sample of 32 data. The type of data is secondary data sourced from financial report data and annual reports. The data analysis method used is multiple linear regression analysis. The findings of this study are based on the results of the t test, it can be concluded that partially DER and firm size have no significant effect on profit growth in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) 2016-2019 . Partially ROA has a significant effect on profit growth in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) 2016-2019. And based on the results of the F test, it is concluded that DER, ROA and firm size simultaneously have a significant effect on profit growth in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) 2016-2019.